OPOSISI PENULISAN HADIS DI BASRAH PADA ABAD KEDUA HIJRIAH - Anshori, Muhammad (IAIN Kediri, 2019)
This paper analyzes the opposition or objection of the writing of hadith ini the second century Hijri in Basrah. By using the historical approach and theory of Walter J. Ong?s orallity and literacy, it was found that since the time of the pophet was still alive, the wring of hadith has indeed became a problem among the companions (?a??bah). This continued during the time of the companions, tabi?in, t?bi? al-t?bi??n, untill there was widespread distribution of hadith accured since some champanions lived in Basrah during the caliph of ?Umar bin al-Kha???b (d. 23 H/644 AD). Historically, many prominent scholars of hadith in Basrah refused to wrote the hadith. They prioritize oral tradition that are closely related to the memorization tradition rather than the written tradition. Oral tradition is indeed very visible in the history of the narration of traditions, giving rise to the term ?abi?. This term shows the power of a narrator?s memorization without relying on writing. In addition to demonstrating the power of memorization, scholars who reject the writing of tradition also avoid meaningful transmission. With the opposition of writing hadith, the narrators who are ?iqah or not can be identified.Key Word: Opposition, Writing of the Hadith, Second Century of Hijri, and Basrah.